Conservation implications of asymmetric introgression and reproductive barriers in a rare primrose species - Ma, Yongpeng (BMC Plant Biol, 2019)
BACKGROUND: Primula is a large genus of flowering herbs well known for their heterostyly. Currently few natural hybrids are known and reproductive barriers in this genus in the wild have received little attention. However, there is instance of hybridization between rare and widely-spread species, and conservation implications of such situation is poorly understood. In the present study, we investigated hybridization patterns and reproductive barriers between a wide spread species, Primula poissonii and a rare species P. anisodora, of which only three populations are currently known. RESULTS: Pollinator-mediated reproductive isolation was strong between parental species but not significant between hybrids and parental species. Hand pollination experiments showed significant reduction of both fruit- and seed-set for heterospecific pollination as compared with conspecific pollination for both parental species. Furthermore, hybrids had higher fruit- and seed-set when pollinated with P. anisodora pollen as opposed to P. poissonii pollen. Microsatellites identified backcrosses to P. anisodora in two of the three populations of P. anisodora, and additionally more individuals of P. anisodora showed introgression from P. poissonii than vice versa. CONCLUSIONS: These results provide evidence for potential genetic swamping of the P. anisodora populations, which could pose a serious threat for this locally endemic species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1881-0) contains supplementary material, which is available to authorized users.